Relationship of tobacco smoking and smoking-related DNA methylation with epigenetic age acceleration - Gao, X.; Y. Zhang; Breitling, L. P.; Brenner, H. (Oncotarget, 2016)
Recent studies have identified biomarkers of chronological age based on DNA methylation levels. Since active smoking contributes to a wide spectrum of aging-related diseases in adults, this study intended to examine whether active smoking exposure could accelerate the DNA methylation age in forms of age acceleration (AA, residuals of the DNA methylation age estimate regressed on chronological age). We obtained the DNA methylation profiles in whole blood samples by Illumina Infinium Human Methylation450 Beadchip array in two independent subsamples of the ESTHER study and calculated their DNA methylation ages by two recently proposed algorithms. None of the self-reported smoking indicators (smoking status, cumulative exposure and smoking cessation time) or serum cotinine levels was significantly associated with AA. On the contrary, we successfully confirmed that 66 out of 150 smoking-related CpG sites were associated with AA, even after correction for multiple testing (FDR <0.05). We further built a smoking index (SI) based on these loci and demonstrated a monotonic dose-response relationship of this index with AA. In conclusion, DNA methylation-based biological indicators for current and past smoking exposure, but not self-reported smoking information or serum cotinine levels, were found to be related to DNA methylation defined AA. Further research should address potential mechanisms underlying the observed patterns, such as potential reflections of susceptibility to environmental hazards in both smoking related methylation changes and methylation defined AA.
Keywords: Aged Aging/*genetics Biomarkers/metabolism Cotinine/blood CpG Islands/physiology DNA Methylation/*physiology Epigenesis; Genetic/*physiology Female Humans Male Middle Aged Self Report Smoking Cessation Tobacco Smoking/*adverse effects/blood Ahrr Gerotarget age acceleration epigenetic clock tobacco smoking whole blood sample